2019
DOI: 10.1021/acsaem.9b01279
|View full text |Cite
|
Sign up to set email alerts
|

Different Pathways for CO2 Electrocatalytic Reduction by Confined CoTMPyP in Electrodeposited Reduced Graphene Oxide

Abstract: Cobalt [5,10,15,20-(tetra-N-methyl-4-pyridyl) porphyrin] (CoTMPyP) was immobilized in reduced graphene oxide (rGO) films by a one-step electroreduction of a self-assembled emulsion of GO and CoTMPyP. These coatings showed remarkable stability for CO2 reduction to both CO and HCOO–, obtained in the gas and liquid electrolyte phases, respectively, with faradaic efficiencies of 45 and 24.3%, respectively, at −0.7 V vs RHE. The unexpected high production of formate and detection of H2 leads to the conclusion that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 59 publications
3
14
0
Order By: Relevance
“…However, we previously incorporated CoTMPyP in reduced graphene oxide (rGO) and reported on considerable produced concentrations of CO and formate for CO 2 RR electrocatalyzed by CoTMPyP/rGO coatings on GC electrodes in neutral electrolyte solution. [33] The presence of carboxyl groups in the rGO coatings acting as proton shuttles and promoting the formation of a hydride complex intermediate was proposed. The protective environment provided by the inner coating layers was suggested to increase the stability of the hydride complex and consequently to increase selectivity towards CO 2 RR over the competing reaction of the hydride with H 2 O to produce H 2 .…”
Section: Resultsmentioning
confidence: 99%
“…However, we previously incorporated CoTMPyP in reduced graphene oxide (rGO) and reported on considerable produced concentrations of CO and formate for CO 2 RR electrocatalyzed by CoTMPyP/rGO coatings on GC electrodes in neutral electrolyte solution. [33] The presence of carboxyl groups in the rGO coatings acting as proton shuttles and promoting the formation of a hydride complex intermediate was proposed. The protective environment provided by the inner coating layers was suggested to increase the stability of the hydride complex and consequently to increase selectivity towards CO 2 RR over the competing reaction of the hydride with H 2 O to produce H 2 .…”
Section: Resultsmentioning
confidence: 99%
“…155 Several carbon-based materials have been used for the immobilization of Co porphyrins, including gas diffusion electrodes (GDE), 156 pyrolytic graphite (PG) 51 and reduced graphene oxide (rGO). 157 In the latter case, the carboxyl groups of the rGO film have been proposed to strongly interact with the cobalt [5,10,15,20-(tetra-N-methyl-4-pyridyl)porphyrin] (CoTMPyP, 24) catalyst, inducing the formation of a hydride intermediate species that would be responsible for an unexpected non-negligible formate production. 157 In addition to the interaction between the catalyst and the support, the pH is a crucial factor to control selectivity.…”
Section: Cobaltmentioning
confidence: 99%
“…157 In the latter case, the carboxyl groups of the rGO film have been proposed to strongly interact with the cobalt [5,10,15,20-(tetra-N-methyl-4-pyridyl)porphyrin] (CoTMPyP, 24) catalyst, inducing the formation of a hydride intermediate species that would be responsible for an unexpected non-negligible formate production. 157 In addition to the interaction between the catalyst and the support, the pH is a crucial factor to control selectivity. A recent study of a Co protoporphyrin (25) immobilized on PG (CoPP/ PG) revealed that small amounts of CH 3 OH (6e) and CH 4 (8e) can be formed in addition to CO in water at moderate overpotential (ca.…”
Section: Cobaltmentioning
confidence: 99%
“…According to the previous reports, the addition of suitable polymer could enhance the properties of the catalyst, such as increasing conductivity, high surface area, outstanding mechanical strength and remarkable stability. Bochlin et al [98] . reported the use of cobalt [5,10,15,20‐(tetra‐N‐methyl‐4‐pyridyl) porphyrin] (CoTMPyP) and reduced graphene oxide (rGO) films that prepared by one‐step electrodeposition to form a self‐assembled catalyst.…”
Section: Co2 Reduction On Different Electro‐synthesized Catalystsmentioning
confidence: 99%
“…According to the previous reports, the addition of suitable polymer could enhance the properties of the catalyst, such as increasing conductivity, high surface area, outstanding mechanical strength and remarkable stability. Bochlin et al [98] reported the use of cobalt [5,10,15,20-(tetra-N-methyl-4-pyridyl) porphyrin] (CoTMPyP) and reduced graphene oxide (rGO) films that prepared by one-step electrodeposition to form a selfassembled catalyst. Their result suggested that the carboxyl groups from the rGO coating could promote the transformation of protons and increase the formation of intermediates, which led to an increase in CO 2 RR activity.…”
Section: Composite Catalystsmentioning
confidence: 99%